Ecdysones from Zoanthus spp. with inhibitory activity against dengue virus 2. Issue 9 (1st May 2016) - Cheng, Yuan-Bin; Lee, Jin-Ching; Lo, I-Wen; Chen, Shu-Rong; Hu, Hao-Chun; Wu, Yu-Hsuan; Wu, Yang-Chang; Chang, Fang-Rong
Graphical abstract: Abstract: Bioassay-guided fractionation of an ethanolic extract of Zoanthus spp. collected in Taiwan has resulted in the isolation of one new ecdysone, zoanthone A (1 ), along with thirteen known compounds (2 –14 ). The structures of these compounds were determined by spectroscopic methods, especially 2D NMR analyses. The in vitro antiviral activities of all isolated ecdysones (1 –14 ) against dengue virus type 2 (DENV-2) were evaluated using DENV infectious system. New compound (1 ) exhibited potent antiviral activity (EC50  = 19.61 ± 2.46 μM) with a selectivity index (CC50 /EC50 ) value of 36.7. The structure–activity relationships of isolated ecdysones against DENV-2 were concluded. Molecular docking information of3 and NS5 polymerase was performed either.